1985
DOI: 10.1063/1.448676
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure of the calcium monohalides. A ligand field approach

Abstract: The electronic structure of the calcium monohalides is addressed using a ligand field model which approximates the halide as a polarizable negative charge perturbing the one electron valence structure of the Ca+ ion. A simple, zero-free-parameter model is shown to predict accurately electronic energies, transition moments, permanent dipole moments, and several other molecular constants that have been experimentally determined. The molecular properties and electronic wave functions are interpreted in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(98 citation statements)
references
References 46 publications
2
94
2
Order By: Relevance
“…The decay branching ratios to different electronic states scale as |d ij | 2 ν 3 ij . The dipole transition moments have been estimated via ligand field modeling [32] and the transition frequencies are known [33], so the ratio of decay rates to the can be estimated:…”
Section: Calcium Monofluoride a Structure And Parametersmentioning
confidence: 99%
“…The decay branching ratios to different electronic states scale as |d ij | 2 ν 3 ij . The dipole transition moments have been estimated via ligand field modeling [32] and the transition frequencies are known [33], so the ratio of decay rates to the can be estimated:…”
Section: Calcium Monofluoride a Structure And Parametersmentioning
confidence: 99%
“…[6,[13][14][15] To study the structure and dynamics of the molecular Rydberg states with both high resolution and a fast data acquisition rate, we incorporate two cru- (ii) The BaF molecular beam generated from our buffer gas cooled ablation source is a factor of 1000 brighter and has 10 times slower laboratory frame velocity than a BaF beam generated by our Smalley-type supersonic jet ablation source. Exploitation of the broad bandwidth, multiplexed, FID-detection scheme would have been impractical without the enhanced brightness of the buffer gas cooled ablation source.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are good candidates for comprehensive laser spectroscopic studies [9,10] because the ionization potentials of their Rydberg series are relatively low (, 5 -6 eV). The ground state and the valence excited A, B, and C states of these molecules were described by Rice et al [5] using a ligand-field model and by Törring et al [6] using an electrostatic polarization model. d'Incan et al [11,12] experimentally observed some excited states of CaF.…”
Section: Introductionmentioning
confidence: 99%